Issues Regarding the Appropriateness of Using Precast Reinforced Concrete Frame Structures Compared to Monolithic Reinforced Concrete Frame Structures, in Office Buildings and Residential Buildings - Bogdan Hauşi Sorin (Bulletin of the Polytechnic Institute of Jassy: Constructions, Architechture Section)
Given the current context at national and European level in terms of reducing skilled labour force in constructions, as well as the high level of density and traffic in large cities, there is an increasing emphasis on the possibility of shortening the duration of building the structural frames on site, reducing the number of workers or even reducing the level of noise pollution. Thus, the introduction of precast technologies in the case of office buildings and residential buildings, with multi-storey frame structure, is becoming an increasingly pressing and topical issue.